Etiology of phomopsis root rot in soybean - Ghissi,Valéria Cecília (2014)
In a survey of damages caused by soybean root rot to crops in the south of Brazil for several years, a root rot caused by Phomopsis sp has been found with increasing frequency. The primary symptoms are seen when the main root is cut longitudinally, including the death of the wood which shows white coloration and well-defined black lines that do not have a defined format. Thus, based on similarity, it has been called geographic root rot due to its aspect resembling irregular lines that separate regions on a map. In isolations, colonies and alpha spores of Phomopsis have prevailed. Pathogenicity test was done by means of inoculation in the crown of plants cultivated in a growth chamber. The geographic symptoms were reproduced in plants and the fungus Phomopsis sp. was reisolated. In soybean stems naturally infected with pod and stem blight, geographic symptoms caused by Phomopsis phaseoli are found. To the known symptoms on stems, pods and grains, that of root rot caused by P. phaseoli is now added.